Lateral Alveolar Ridge Augmentation with Autogenous Tooth Block Graft Compared with Autogenous Bone Block Graft: a Systematic Review - Thomas Starch-Jensen; Julie Vitenson; Daniel Deluiz; Kimie Bols Østergaard; Eduardo Muniz Barretto Tinoco (eJournal of Oral Maxillofacial Research)
Objectives: The objective of the present systematic review was to evaluate the current knowledge of implant treatment outcome following lateral alveolar ridge augmentation with autogenous tooth block graft compared with autogenous bone block graft prior to implant placement.